6s-11=-2s+5
+2s +2s
8s-11=5
+11 +11
8s=16
/8 /8
s=2
Check:
6(2) - 11 = -2(2) + 5
12 - 11 = -4 + 5
1=1
2006-12-06 13:07:49
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
6s-11=-2s+5
6s+2s-11=-2s+2s+5
8s-11=5
8s-11+11=5+11
8s=16
s=16/8
s=2
2006-12-06 13:16:27
·
answer #2
·
answered by elli 1
·
0⤊
0⤋
6s-11=-2s+5
+2s =+2s
8s-11= 5
+11= +11
8s/8=16/8
s=2
2006-12-06 13:10:53
·
answer #3
·
answered by sk8er V 2
·
0⤊
0⤋
6s-11=-2s+5
6s+2s=5+11
8s=16
s=16/8
s=2
2006-12-06 13:30:46
·
answer #4
·
answered by sam 3
·
0⤊
0⤋
6s-11=-2s+5
8s-11=5
8s=16
s=2
2006-12-06 13:11:44
·
answer #5
·
answered by n_m_young 4
·
0⤊
0⤋
6s-11=-2s+5
+2s +2s the 2 will cancel out
_____________________
8s-11=5
+11=+11 the 11 will cancel out
______________________
8s=16
divide by 8
s=2
2006-12-06 13:12:09
·
answer #6
·
answered by katie 4
·
0⤊
0⤋
8s-11=5
8s=16
s=2
2006-12-06 13:08:27
·
answer #7
·
answered by lulu 3
·
0⤊
0⤋
s=2
sry, looked like a regular 2s
2006-12-06 13:08:11
·
answer #8
·
answered by DonSoze 5
·
0⤊
0⤋
Simultaneously transposing terms, we get:
8s = 16
Dividing both sides by the coefficient of the unknown,
that is, by 8, we get:
s = 2
2006-12-06 15:43:45
·
answer #9
·
answered by jerryinchelsea 2
·
0⤊
0⤋